Knowledge and behavioral attitudes of the academic community of the high school and university levels towards the prevention of covid-19: a cross-sectional study in Guasave, Sinaloa - Peinado-Guevara, Víctor Manuel; Cuadras Berrelleza, Aldo Alan; Herrera-Barrientos, Jaime; Héctor José, Peinado-Guevara; Izaguirre-Gámez, Samuel Doeg; Urias-Camacho, Alejandro (Technium Social Sciences Journal, 2021)
The COVID-19 pandemic impacts, worldwide, the daily activities of the population, in view of this, various preventive measures have been adopted to reduce the risks of contagion. In the educational field in Mexico, face-to-face classes have been suspended, adopting the use of electronic platforms; this, to avoid the risks of contagion. Measures like the aforementioned, the use of face masks, gels, healthy distance, face shields, among others, are already part of the daily routine. However, the level of perception, responsibility and behavior in the face of these measures by the various sectors of the population is unknown. In this study, the perception of high school and university students from Guasave, Sinaloa, Mexico is analyzed. To know the aforementioned aspects, a descriptive cross-sectional study was carried out using the convenience sampling technique, applying a survey made up of 18 items of Likert-type, designed on the Google Forms platform, to a sample of 940 students of both sexes, in 10 public and private schools. The results show that, more than 50% of the students of both educational levels, have a perception that deviates from reality, they do not measure the importance of the preventive measures that the health sector recommends to reduce the contagion and lethality rate. Despite recognizing that the viral disease is contagious, they do not perceive the importance of measures such as washing hands with soap, using gels, masks, face masks, maintaining a healthy distance, among other sanitary measures. They assume the measure of confinement as necessary, although it generates stress and a decrease in their academic performance, reflected in low grades. The results found in the studied educational sector indicate that the educational authorities should strengthen the scientific learning of the students in relation to the epidemiological phenomenon of covid-19, in order to contribute to their conduct and implementation of health protection measures and prevention of this scourge.